2017
DOI: 10.1186/s12963-017-0137-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the global contribution of alcohol consumption to cardiomyopathy

Abstract: BackgroundThe global impact of alcohol consumption on deaths due to cardiomyopathy (CM) has not been quantified to date, even though CM contains a subcategory for alcoholic CM with an effect of heavy drinking over time as the postulated underlying causal mechanism. In this feasibility study, a model to estimate the alcohol-attributable fraction (AAF) of CM deaths based on alcohol exposure measures is proposed.MethodsA two-step model was developed based on aggregate-level data from 95 countries, including the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
0
15
0
1
Order By: Relevance
“…On the other hand, the estimates that account for underlying causes of death only can be considered estimates of the minimum burden of alcohol on mortality. In addition, causes of death wholly attributable to alcohol may not be fully recorded in death certificates due to stigma associated with alcohol-related health problems, which has been shown to be the case at least for alcoholic liver cirrhosis and alcoholic cardiomyopathy [ 39 , 40 ]. One of the approaches using underlying causes of death included all underlying liver cirrhosis ( main underlying ), and showed a similar age-specific pattern as the other underlying cause-of-death approaches (except the HFA-DB ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the estimates that account for underlying causes of death only can be considered estimates of the minimum burden of alcohol on mortality. In addition, causes of death wholly attributable to alcohol may not be fully recorded in death certificates due to stigma associated with alcohol-related health problems, which has been shown to be the case at least for alcoholic liver cirrhosis and alcoholic cardiomyopathy [ 39 , 40 ]. One of the approaches using underlying causes of death included all underlying liver cirrhosis ( main underlying ), and showed a similar age-specific pattern as the other underlying cause-of-death approaches (except the HFA-DB ).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic alcohol abuse is an important cause of DCM, occurring most often in men of 30-55 years of age who have been heavy consumers of alcohol for at least 10 years 110 . The proportion of alcoholic cardiomyopathy among all cardiomyopathy deaths was estimated at 6.9% globally 111 , and alcoholic DCM occurred more often in men (8.9%) than in women (2.9%). Studies in animals have demonstrated that acute and chronic ethanol administration impairs cardiac contractility 112 and decreases the contractile protein α-myosin heavy chain 110 .…”
Section: Chemical and Toxin Exposurementioning
confidence: 99%
“…In some former Soviet countries including Belarus, Kyrgyzstan, Russia and Ukraine, autopsies have been legally required for deceased persons under a certain age threshold 10. As autopsies are vital for recognising cardiomyopathy (described in detail below) and form an important step in classification of ACM as cause of death, detection rate of ACM might be above average in these countries.…”
Section: Discussionmentioning
confidence: 99%
“…The methods used were developed and described in detail elsewhere 10. We will restrict ourselves to sketching out the main modelling strategy here.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation